Fostering Religious Tolerance Through The Values of An-Nahdliyah - Achmad Saepurridjal; Hendi Suhendraya Muchtar; Hanafiah Hanafiah; Muhammad Andriana Gaffar; Ahmad Khori; Luki Luqmanul Hakim (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2021)
A plurality of, is fitroh divine so that mutual respect and keep security as well as guyup pillars, the rule obliges every citizen to embrace one religion that has been specified by the the ministry of religion's existence. The purpose of this research is for dig up information about the educational institutions of the boarding school in investment value-the value of the ahl as-sunnah wal jama'ah through the program religious activities. In this study use a qualitative approach with methods the study of the instrumental case. Based on the results of the research, it is known that: 1) Policies that underlying the program development of tolerance, a) the concept of at-tawasuth, b), the concept of knowing,, c, the concept tawazun, d), the concept of tasamuh, 2) the Fostering, a), Aswaja knowing, b), Aswaja feeling. c), Aswaja Action, 3) Implementation a) Introduce and familiarize students interact with people of other faiths. b) Giving example about the attitude tolerance by the kyai, c) Through learning in Boarding school, 4) Positive impact the form of the impartiality the students in interact 5) the Problems that arise a) lack of supervision b) Most of the students have the activities double, c) lodging at boarding schools already start damaged. Strategy conceptual practical tips is a step to carry out program investment value-the value of the ahl as-sunnah wal-jama'ah to students.